Gender differences in financial knowledge, attitudes, and behaviors: Accounting for socioeconomic disparities and psychological traits. Issue 3 (30th June 2020) - Robson, Jennifer; Peetz, Johanna
Abstract: A large body of international research finds a persistent gender gap in the financial literacy of women compared to men, but explanations for this gap remain a topic of active debate. In this observational study, we explore the explanatory value of psychological characteristics, in addition to demographic variables and roles in household financial decision making. We begin by documenting the expected gender differences in financial knowledge, attitudes, and behaviors, using a national survey of adult Canadians ( n = 21, 789) that provides population‐level estimates. Next, we contrast these results against a second Canadian survey data set ( n = 3, 502) where we are able to control for individual differences in psychological traits. Results of OLS regressions suggest that gender is not a significant predictor on three scales of financial capability. Decomposition analysis finds underlying differences in individual characteristics (endowments) explain the majority of the observed gender gap in financial literacy when psychological traits are included in the model.